World experience of public administration land use and protectiontaking into account the requirements of ecological safety - Sviridova, L. (Land Management, Cadastre and Land Monitoring, 2017)
Studied global trends of public administration land use and protection. In particular, zemleohoronni measures in the developed world are implemented through rural development policy, based on the conduct of the common agricultural policy, the creation of funds to support farmers, provide technical assistance, development of national programs and future development plans. For the European Union development policy documents on the development of land areas for 5-10 years - the overall trend. Land management activities are conducted in foreign countries on the basis of approved design documentation for land management different direction. Found that the use of land and resource potential in the world is subject to the requirements of environmental safety. Agrarian relations in these countries are based on incentive levers, with direct execution of the rules of use and protection of land. By 2020, the strategy of the Common Agricultural Policy of the European Union provides funding for joint agricultural market, direct subsidies to farmers and stimulate agricultural development. Common Agricultural Policy of the European Union for its activities fully demonstrates the ability of European economies to maintain the same level of development. State administration of environmental impact on the economic interests of the tenure or land use in countries with market economies include: tax exemptions (to make environmentally oriented activities), soft loans (available on interest rates for environmental investments), subsidies (for the implementation of environmental programs ) and subsidies (for growing products without pesticides) entities. It is proved that the system of economic instruments in environmental policy Ukraine needs to improve, because it is poorly developed. Experience in other countries shows that as we strengthen land management tools (instruments for land administration), and its supporting tools to succeed in the system of rational land use. By tools include: a) political system; b) planning of land use; c) the economic and legal methods of state regulation of land relations and land market; d) guarantee of land ownership, land ownership and land use, taxation of land. By supporting tools include: a) the registration of rights to land, b) land cadastre) the arrangements for evaluation, accounting and inventory of land use and others. For the improvement of the economic levers offer: 1) to work out mechanisms refund agrarian agricultural land ownership and land use using innovative technologies for the conservation and protection of soil; 2) simplify the subsidies, grants, benefits for land users at the expense of local budgets (from the land tax and compensation of losses of agricultural and forestry production); 3) Improve mechanisms to stimulate rational land use. In addition, it is believed that it should be the private owners of the major organizations that implement environmental policy for the protection of land and carrying out effective environmental management due to their ownership or land use. Therefore, at the state level need to develop a program to encourage private sector agricultural producers. Key words: public administration of land use and protection, ecological security, foreign countries, world experience